2016
DOI: 10.1021/acsinfecdis.5b00141
|View full text |Cite
|
Sign up to set email alerts
|

A Redox-Active Fluorescent pH Indicator for Detecting Plasmodium falciparum Strains with Reduced Responsiveness to Quinoline Antimalarial Drugs

Abstract: Mutational changes in the Plasmodium falciparum chloroquine resistance transporter (PfCRT) have been associated with differential responses to a wide spectrum of biologically active compounds including current and former quinoline and quinoline-like antimalarial drugs. PfCRT confers altered drug responsiveness by acting as a transport system, expelling drugs from the parasite's digestive vacuole where these drugs exert, at least part of, their antiplasmodial activity. To preserve the efficacy of these invaluab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 66 publications
0
13
0
Order By: Relevance
“…It is therefore possible that the passage of other molecules through the NPC indirectly influences the action of these drugs (e.g., by changing drug activation or accumulation in the FV). For instance, glucose depletion influences FV pH (Saliba et al, 2003), which affects drug accumulation of some 4-AQs (Jida et al, 2017;Yayon et al, 1984). However, MFQ, which may have a different mode and site of action than other 4-AQs (Cowman et al, 1994;Wong et al, 2017), was still dependent on the NPCs in our assay , arguing against an indirect effect based on mode of action.…”
Section: Drugs Pass Through the Pvm Npcsmentioning
confidence: 72%
“…It is therefore possible that the passage of other molecules through the NPC indirectly influences the action of these drugs (e.g., by changing drug activation or accumulation in the FV). For instance, glucose depletion influences FV pH (Saliba et al, 2003), which affects drug accumulation of some 4-AQs (Jida et al, 2017;Yayon et al, 1984). However, MFQ, which may have a different mode and site of action than other 4-AQs (Cowman et al, 1994;Wong et al, 2017), was still dependent on the NPCs in our assay , arguing against an indirect effect based on mode of action.…”
Section: Drugs Pass Through the Pvm Npcsmentioning
confidence: 72%
“…The comparative analysis of the above cysteine modifications showed that these were detectable only in gametocyte-infected RBC treated with 1 and not with 4, suggesting that the complete reduction of the 7-nitro group of 1 to its 7-amino counterpart likely takes place only after the previous adduct formation step(s). Recent observations that NBD derivatives are substrates of NADPH-dependent P. falciparum oxidoreductases led to propose a role for these molecules as "redox cyclers", i.e., compounds depleting the cell cytosol reducing power [41]. This may lead to speculate that gametocyte enzymes, yet to be identified, are likely responsible for the nitroreduction process that seems to be involved in the generation/stabilization of the adducts between 1 and cysteine residues.…”
Section: Discussionmentioning
confidence: 99%
“…According to Jida et al, (2016) the accumulation of Fluo-CQ, a pH-sensitive fluorescent chloroquine analog in the DV did not occur in the glucose-free medium. This was due to the lack of energy input to acidify the DV, which is necessary for the accumulation and trapping of Fluo-CQ in the DV.…”
Section: A (I) a (Iii) A (Ii) Bmentioning
confidence: 99%
“…This was due to the lack of energy input to acidify the DV, which is necessary for the accumulation and trapping of Fluo-CQ in the DV. The acidification of DV was observed through the strong fluorescence signal of Fluo-CQ 23 .…”
Section: A (I) a (Iii) A (Ii) Bmentioning
confidence: 99%